Readthrough of SCN5A Nonsense Mutations p.R1623X and p.S1812X Questions Gene-therapy in Brugada Syndrome - Teng, Siyong; Huang, Jian; Gao, Zhan; Hao, Jie; Yang, Yuejin; Zhang, Shu; Pu, Jielin; Hui, Rutai; Wu, Yongjian; Fan, Zheng (Current Gene Therapy, 2017)
Purpose: Nonsense mutation readthrough is used as a gene-specific treatment in some genetic diseases. The response to readthrough treatment is determined by the readthrough efficiency of various nonsense mutations. In this manuscript, we aimed to explore the harmful effects of nonsense mutation suppression. Methods: HEK293 cells were transfected with two SCN5A (encode cardiac Na+ channel) nonsense mutations, p.R1623X and p.S1812X. We applied two readthrough-enhancing methods (either aminoglycosides or a siRNA-targeting eukaryotic release factor eRF3a (a GTPase that binds eRF1)) to suppress these SCN5A nonsense mutations. When either of readthrough methods was used, the sodium channel proteins were examined by western blot and immunoblotting and recorded by whole cell patch-clamp to observe the functional characterization of the restored channels. Results: Upon readthrough treatment, the sodium currents were restored to the mutant cDNAs. These mutations reduced full-length sodium channel protein levels, and the sodium currents were reduced to 3% of wild-type. The mutant cDNA sodium currents were increased to 30% of wild-type, and the fulllength proteins also increased. However, the functional characterization of these channels from cDNAs carrying p.R1623X and p.S1812X exhibited abnormal biophysical properties, including a negative shift in steady-state sodium channel inactivation, a positive shift in sodium channel activation and robust late sodium currents. The ramp test showed prolonged QT intervals. Conclusion: These results demonstrated that readthrough-enhancing methods effectively suppressed nonsense mutations in SCN5A and restored the expression of full-length channels. However, the restored channels may increase the risk of arrhythmia.
Keywords: readthrough